2016
DOI: 10.1186/s12879-016-1815-5
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ treatment-seeking behaviors and predictors of whether a child received an appropriate antimalarial treatment: a household survey in rural Uganda

Abstract: BackgroundThis study responds to a rural community’s concern that, despite national initiatives, malaria management in young children falls short of national guidelines in their district. This study aimed to: (1) describe caregivers’ treatment-seeking behaviors in the rural district of Butaleja, (2) estimate the percentage of children who received an appropriate antimalarial, and (3) determine factors that maximized the likelihood of receiving an appropriate antimalarial. Appropriate antimalarial in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 20 publications
(22 reference statements)
1
30
0
Order By: Relevance
“…Data from a cross-sectional household survey conducted in 2011 and ten psychometrically justified scales were used to estimate assets and challenges facing caregivers when managing malaria in children 5 years and under in Butaleja District, Uganda [ 14 ]. Ethics approval for the project and written informed consent from participants was obtained prior to conducting the surveys.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data from a cross-sectional household survey conducted in 2011 and ten psychometrically justified scales were used to estimate assets and challenges facing caregivers when managing malaria in children 5 years and under in Butaleja District, Uganda [ 14 ]. Ethics approval for the project and written informed consent from participants was obtained prior to conducting the surveys.…”
Section: Methodsmentioning
confidence: 99%
“…A purposive, multi-step sampling process was used to ensure representation across all ten sub-counties and two town councils [ 14 ]. The sampling process considered size of villages, religious denominations, dominant tribes, and proximity to a government health centre.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies concluded that this decline in malaria-related care would threaten the control of the disease in Guinea [18][19][20]. This threat is reflected here by the still high recourse to traditional healers for the management of fever and by the no-recourse which, according to Kassam et al [21], would be associated with a tendency to self-medication and by non-confidence in traditional healers. Yet, the impact of economic and socio-cultural barriers on the decision to seek treatment should not be overlooked.…”
Section: Epidemiology and Infection 1991mentioning
confidence: 99%